The Identity of Widowed Women in the Digital Era - Ulfi Nurfaiza; A. Fikri Amiruddin Ihsani (PT Agung Media Publisher, 2024)
The digital era has significantly changed the perspectives and ways of communication for individuals, including women with widow status. Previously, during the patriarchal era, cultural values and norms established that widowed women faced more severe life challenges and received negative stigmas. According to data from DataIndonesia.id, the percentage of widows in Indonesia was higher than that of widowers in 2021. Divorced women accounted for 12.83% of the population, including those divorced by death or alive. Meanwhile, the percentage of divorced men was 4.32%. The digital era has impacted social changes, with the high number of widowed women indicating that women now have greater opportunities to enhance their capacities, which also affects their economic fulfillment. This research aims to understand the identity of widowed women in the digital era in terms of externalization, objectivation, and internalization. The study employs a qualitative approach using social construction. Data collection techniques include in-depth interviews, observations, and documentation. The findings of this research indicate that widowed women feel that their role teaches them the meaning of independence, allowing them to work or pursue careers without limitations. They can optimize social media as a platform to enhance their quality and relationships, and others acknowledge that these women are comfortable and confident with their current status. Being a widow is no longer something to be feared or constantly stigmatized; it has evolved with the development of technology and information.